Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3168/jds.2008-1634
|View full text |Cite
|
Sign up to set email alerts
|

Performance and metabolic and endocrine changes with emphasis on glucose metabolism in high-yielding dairy cows with high and low fat content in liver after calving

Abstract: Elevated liver fat content occurs in high-yielding dairy cows during the transition from pregnancy to lactation after fat mobilization and may affect hepatic glucose metabolism, but the degree of liver fat storage is highly variable. Therefore, we studied metabolic and endocrine changes and hepatic glucose metabolism in cows that markedly differ in liver fat content. Multiparous cows from the same herd with high (HFL; n = 10) and low (LFL; n = 10) liver fat contents (mean of d 1, 10, and 21 after calving for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
161
3
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(212 citation statements)
references
References 43 publications
37
161
3
6
Order By: Relevance
“…Insulin concentrations were determined by RIA as described by van Dorland et al (2009). Glucagon concentration was detected by RIA using a kit from Linco (GL-32K; Linco Research, St. Charles, MO; Hammon et al, 2009).…”
Section: Blood Sampling and Analyses Of Metabolites And Hormonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin concentrations were determined by RIA as described by van Dorland et al (2009). Glucagon concentration was detected by RIA using a kit from Linco (GL-32K; Linco Research, St. Charles, MO; Hammon et al, 2009).…”
Section: Blood Sampling and Analyses Of Metabolites And Hormonesmentioning
confidence: 99%
“…High rates of fat mobilization lead to markedly increased plasma concentrations of NEFA and, in consequence, the accumulation of triglycerides (TAG) in the liver (Bobe et al, 2004;Overton and Waldron;2004). Recent research has suggested considerable variation among high selected dairy cows for releasing energy fuels from stored adipose tissues (Chilliard et al, 2000;Hammon et al, 2009). Tamminga et al (1997) observed great differences among cows in fat mobilization during the first 8 wk of lactation, ranging from 8 to 57 kg of body fat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, statistical differences of 'backfat thickness' are due to the greater skin thickness (D0) observed in MONT, which became evident after the depletion of subcutaneous adipose and connective tissues (D1 − D0) postpartum. 'Backfat thickness' is correlated with total body fat (Schroder and Staufenbiel, 2006), and allowed to differentiate body reserve mobilization among cows that calve with different degree of body fatness (Hammon et al, 2009;Weber et al, 2013). However, it does not take into account internal adipose depots, which may have different dynamics of mobilization during early lactation (Weber et al, 2013).…”
mentioning
confidence: 99%
“…It is noteworthy that transition dairy cows (cows in the period from three weeks before to three weeks after parturition) experience a negative energy balance (NEB) [37,38]. This arises from the increased energy demands at parturition, especially due to their genetic potential to produce high levels of milk.…”
Section: The Benefit Of Using Feed Supplements: Why the Feed Industrymentioning
confidence: 99%